2014
DOI: 10.1158/0008-5472.can-13-2420
|View full text |Cite
|
Sign up to set email alerts
|

HIC1 Silencing in Triple-Negative Breast Cancer Drives Progression through Misregulation of LCN2

Abstract: The tumor suppressor gene HIC1 is frequently deleted or epigenetically silenced in human cancer, where its restoration may improve cancer prognosis. Here, we report results illuminating how HIC1 silencing alters effect or signals in triple-negative breast cancer (TNBC), which are crucial for its pathogenesis. HIC1 expression was silenced only in TNBC compared with other molecular subtypes of breast cancer. Restoring HIC1 expression in TNBC cells reduced cell migration, invasion, and metastasis, whereas RNAi-me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…Efficient overexpression of HIC1 in MCF-7 cells was achieved (Supplementary Figures S4A and S4C). In agreement with previous findings, 16, 17 overexpression of HIC1 in MCF-7 cells indeed caused increased cell apoptosis and decreased cell invasion (Figures 3d–g), indicating that HIC1 and miR-23a~27a~24-2 cluster have the opposite effect on cell apoptosis and invasion. More importantly, apoptosis and invasion assays revealed that ectopic expression of miR-23a~27a~24-2–resistant HIC1 dramatically attenuated the inhibitory effect of the miR-23a~27a~24-2 cluster on cell apoptosis and stimulatory effect on cell invasion (Figures 3d–g).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Efficient overexpression of HIC1 in MCF-7 cells was achieved (Supplementary Figures S4A and S4C). In agreement with previous findings, 16, 17 overexpression of HIC1 in MCF-7 cells indeed caused increased cell apoptosis and decreased cell invasion (Figures 3d–g), indicating that HIC1 and miR-23a~27a~24-2 cluster have the opposite effect on cell apoptosis and invasion. More importantly, apoptosis and invasion assays revealed that ectopic expression of miR-23a~27a~24-2–resistant HIC1 dramatically attenuated the inhibitory effect of the miR-23a~27a~24-2 cluster on cell apoptosis and stimulatory effect on cell invasion (Figures 3d–g).…”
Section: Resultssupporting
confidence: 93%
“…15 HIC1, a tumor-suppressor gene that is downregulated in many human cancers, 16 was identified as an ideal candidate. The predicted interactions between miR-23~27~24 clusters and HIC1 3′-UTR are illustrated in Figure 2a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, HIC-1 mRNA and protein levels were reported to be low or absent in pancreatic ductal adenocarcinoma (PDAC) tissues, and its expression gradually decreased during the progression of PDAC; negative HIC-1 expression predicted advanced pathological stage and poor patient survival [25]. Moreover, HIC-1 expression was found to be silenced in triple-negative breast cancer [24]. Although studies have identified HIC-1 as having frequent changes in hypermethylation or loss of heterozygosity in many human cancers [40, 41], the molecular mechanisms through which HIC-1 inhibits cancer progression remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis of miR - 4532 has shown that hypomethylated in cancer-1 (HIC-1) may be an miRNA target gene involved in the regulation of resistance of cancer cells to chemotherapeutic drugs. The HIC - 1 gene, located on chromosome 17p13.3, is a tumor-suppressor gene that is frequently silenced or deleted in a variety of human cancers, such as leukemia, liver cancer, pancreatic cancer, and breast cancer [2124]. HIC-1 is involved in several complex biological functions in the regulation of drug resistance in cancer, including cell survival, cell growth, cell motility, and cell migration [25].…”
Section: Introductionmentioning
confidence: 99%